2014
DOI: 10.1038/ng.3080
|View full text |Cite
|
Sign up to set email alerts
|

The Scc2–Scc4 complex acts in sister chromatid cohesion and transcriptional regulation by maintaining nucleosome-free regions

Abstract: The cohesin complex is at the heart of many chromosomal activities, including sister chromatid cohesion and transcriptional regulation1-3. Cohesin loading onto chromosomes depends on the Scc2/Scc4 cohesin loader complex4-6, but the chromatin features that form cohesin loading sites remain poorly understood. Here, we show that the RSC chromatin remodeling complex recruits budding yeast Scc2/Scc4 to broad nucleosome-free regions, that the cohesin loader itself helps to maintain. Consequently, inactivation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
168
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(185 citation statements)
references
References 51 publications
15
168
2
Order By: Relevance
“…The poly(dA:dT) tract of URA3 plays precisely this role in organizing chromatin (37). The cohesin loading complex (Scc2-Scc4) has been found at A-T rich DNA both in vitro and in vivo (8,38). Together, these findings suggest that the poly(dA:dT) tract helps load functional cohesin complexes that generate cohesion at URA3.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The poly(dA:dT) tract of URA3 plays precisely this role in organizing chromatin (37). The cohesin loading complex (Scc2-Scc4) has been found at A-T rich DNA both in vitro and in vivo (8,38). Together, these findings suggest that the poly(dA:dT) tract helps load functional cohesin complexes that generate cohesion at URA3.…”
Section: Resultsmentioning
confidence: 54%
“…In principle, the A-T rich sequences could act in one of two ways: as a site where functional cohesin complexes are loaded or a site where preloaded, nonfunctional complexes are made competent for cohesion. Recent work showed that the Scc2-Scc4 cohesin loading complex of S. cerevisiae associated with and helped maintain nucleosome free regions like those created by poly(dA:dT) tracts (38). Indeed, the data of LopezSerra et al (38) showed a strong correlation between Scc2-Scc4 binding and the presence of poly(dA:dT) tracts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2D,E). This result suggests the possible involvement of the plant cohesinloading complex in sculpting chromatin of interphase nuclei (Lopez-Serra et al, 2014).…”
Section: Expression and Localization Analysis Of Atscc4mentioning
confidence: 70%
“…In budding yeast, cohesin loads onto chromatin at discrete sites (usually heavily-transcribed genes) and then migrates to distal sites where it accumulates (Lengronne et al 2004;Lopez-Serra et al 2014). In the vicinity of HMR, cohesin loading is mediated by the tRNA gene that demarcates the telomere-proximal, silent chromatin boundary (Dubey and Gartenberg 2007).…”
Section: Potential Cell Cycle Regulators Of Silent Chromatin Establismentioning
confidence: 99%